Feeding spray-dried plasma to broilers early in life improved their intestinal development, immunity and performance irrespective of mycotoxins in feed - Gómez-Verduzco, Gabriela; Arce-Menocal, José; López-Coello, Carlos; Avila-González, Ernesto; Márquez-Mota, Claudia C.; Polo, Javier; Rangel, Luis (Frontiers in Veterinary Science, 2024)
Introduction: Fungi that produce mycotoxins can grow on certain food products, such as grains and feed, and can cause a variety of health issues if consumed by animals, including chickens. The use of spray-dried plasma (SDP) is one strategy for combating the health problems caused by mycotoxins.In the present study, Ross 308 chickens (n = 960) were divided into four treatment groups. T1 group was given a control diet (corn-soybean), T2 group was given a control diet + 2% SDP, T3 group was given a control diet + 2% SDP + mixture mycotoxins and T4 group was givena control diet + mycotoxin mixture.Eliminado: Spray-dried Plasma 30 Eliminado: Mycotoxins;